Biomechanical comparison of the anterior reverse PHILOS and locking compression plate extra-articular distal humerus plates for extra-articular distal humeral fractures - Kritsaneephaiboon, Apipop; Wanchat, Sujin; Khongkanin, Thammaphong; Kwanyuang, Atichart; Srewaradachpisal, Satta; Dissaneewate, Kantapon; Orapiriyakul, Wich (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe locking compression plate extra-articular distal humeral plate (EADHP) is an anatomically pre-contoured plate that is used for extra-articular distal humeral fractures. However, there is currently no standard criterion for the internal fixation of this type of fracture. Moreover, the anterior reverse proximal humeral internal locking system (PHILOS) plate (ARPP) has been clinically applied as a new internal-fixation plate without testing in biomechanical studies. We aimed to compare the biomechanical properties of ARPP and EADHP for the definitive fixation of extra-articular distal humeral fractures.MethodsEighteen composite humerus bones were cut at the distal humerus using an electrical saw to generate a fracture gap. Internal fixation via the ARPP or EADHP was performed following standard techniques. An Instron testing machine (Instron 8872) was used to evaluate biomechanical properties by applying bending torque, axial force, and torsional torque.ResultsFixations with both ARPP and EADHP could withstand forces that exceeded the physiological forces (200 N). Under axial compression, ARPP constructs demonstrated greater stiffness (668.9 ± 120.7 N/mm vs 171.2 ± 45.4 N/mm) and higher maximal load-to-failure (2,092.6 ± 305.2 N vs 907.0 ± 56.5 N) compared with EADHP, although these differences were not statistically significant. During anterior bending, ARPP provided significantly higher stiffness (17.8 ± 2.0 N/mm vs 13.9 ± 1.0 N/mm, p = 0.041), whereas EADHP showed a higher but non-significant load-to-failure. Under torsional loading, ARPP tended to exhibit greater stiffness in both external and internal rotation, as well as higher load-to-failure (31.1 ± 0.8 N m vs 26.0 ± 4.4 N m), but without statistical significance.ConclusionARPP demonstrated superior bending stiffness compared with the EADHP, while both constructs performed equivalently in axial compression and torsion. Therefore, ARPP can serve as an alternative internal-fixation method for extra-articular distal humeral fractures.